UROPATHOGENS: ISOLATION AND ANTIBACTERIAL SUSCEPTIBILITY PATTERN - Kumar, Harit; Insan, Nitin Goel; Chauhan, Shubham; Singh, Varsha A (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: To find the antibiotic sensitivity pattern of uropathogens. Methods: A total of 100 urine samples of clinically suspected urinary tract infection were collected from May 2016 to July 2016. The samples were inoculated on cystine lactose electrolyte deficient agar and incubated at 37Â°C for 24 hrs. Results: A total of 77 (77%) samples were positive showing microbial growth. Among all isolates, Escherichia coli was 36.36%, followed by Klebsiella spp. (35.06%), Citrobacter spp. (6.49%), Staphylococcus aureus (6.49%), Pseudomonas spp. (5.19%), Enterococcus faecalis (3.90%), and Acinetobacter spp. (1.30%). For Gram-positive isolates, the most effective antibiotic was nitrofurantoin followed by sulphafurazole. For Gram-negative isolates, the most effective antibiotic was nitrofurantoin followed by gentamicin and piperacillin/tazobactam. Conclusion: In this study, nitrofurantoin was the most effective antibiotic for Gram-positive and Gram-negative uropathogens